2012
DOI: 10.1175/mwr-d-11-00044.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Vertical Distribution of Mean Vertical Velocities in the Convective Regions during the Wet and Dry Spells of the Monsoon over Gadanki

Abstract: The Indian Mesosphere-Stratosphere-Troposphere (MST) radar observations of vertical distribution of mean vertical velocities w in convective regions during the wet and dry spells of the Indian summer monsoon over a tropical station at Gadanki, India (13.58N, 79.28E) are discussed. The composite w profile during the wet spell consistently shows a single peak at ;13 km whereas during the dry spell it shows two peaks, one at 5 km and another at 11-13 km. The characteristics of this altitudinal distribution in w a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The monsoon season (June to September) appears to be the favorite period for the lifted layers in the stratosphere (fig.13a). This looks to be linked to the vertical lifting associated with severe convection (as seen in our model simulations fig.11 and Mov.1 in supplementary material) and thin tropopause layer as explained earlier (Fu et al, 2006;Randel et al, 2010;Vernier et al, 2011;Thampi et al, 2012;Uma et al, 2012). Additionally, these layers seem to be present during the other seasons (pre-monsoon and winter) as well.…”
Section: Occurrence Of Bc At High Altitudes: Observational Evidencesupporting
confidence: 63%
“…The monsoon season (June to September) appears to be the favorite period for the lifted layers in the stratosphere (fig.13a). This looks to be linked to the vertical lifting associated with severe convection (as seen in our model simulations fig.11 and Mov.1 in supplementary material) and thin tropopause layer as explained earlier (Fu et al, 2006;Randel et al, 2010;Vernier et al, 2011;Thampi et al, 2012;Uma et al, 2012). Additionally, these layers seem to be present during the other seasons (pre-monsoon and winter) as well.…”
Section: Occurrence Of Bc At High Altitudes: Observational Evidencesupporting
confidence: 63%
“…Profiler retrievals from Darwin have further shown that non-precipitating anvil has potentially different vertical motion structure than precipitating stratiform cloud (Protat and Williams, 2011). Other profiler studies have been conducted over southern India and Indonesia (Kumar et al, 2005;Mori et al, 2006;Rao et al, 2009;Uma and Rao, 2009;Abhilash et al, 2010;Uma et al, 2012) and are generally consistent with the Darwin findings. In addition, Giangrande et al (2013) used profiler retrievals to analyse the statistics of deep convective vertical velocities over a midlatitude continental site and found updraught core maxima regularly exceed 10 m s −1 , although downdraught core maxima were skewed to lower values and found at lower heights.…”
Section: Introductionmentioning
confidence: 54%
“…Profiler retrievals from Darwin have further shown that non‐precipitating anvil has potentially different vertical motion structure than precipitating stratiform cloud (Protat and Williams, ). Other profiler studies have been conducted over southern India and Indonesia (Kumar et al ., ; Mori et al ., ; Rao et al ., ; Uma and Rao, ; Abhilash et al ., ; Uma et al ., ) and are generally consistent with the Darwin findings. In addition, Giangrande et al .…”
Section: Introductionmentioning
confidence: 99%
“…10 and Mov. 1 in the Supplement) and thin TTL as explained earlier (Fu et al, 2006;Randel et al, 2010;Vernier et al, 2011;Thampi et al, 2012;Uma et al, 2012). Additionally, these layers seem to be present during the other seasons (premonsoon and winter) as well.…”
Section: Occurrence Of Bc At High Altitudes: Observational Evidencementioning
confidence: 58%